Modern Food Microbiology - Jay, James M Loessner, Martin J Golden, David Allen (Springer, 2005)
"This invaluable and authoritative book will serve as an ideal text for students taking a food microbiology course, particularly within food science, food technology, food science/nutrition/microbiology, biology, or biological science departments. As part of the Food Science Text Series, Modern Food Microbiology incorporates the key subjects required to meet the minimum standards for degrees in food science as developed by the Institute of Food Technologists. In addition, it will provide food scientists with a wealth of practical information about the most essential factors and principles that affect microorganisms in foods."--Jacket.